On Paraconsistent Logic, its Reception in East and West, and on Being a Philosopher. - Dagys, Jonas; Gricius, Pranciškus (Problems / Problemos)
The article "On Paraconsistent Logic, its Reception in East and West, and on Being a Philosopher" is an interview with Graham Priest, a Distinguished Professor of Philosophy, discussing his intellectual journey, paraconsistent logic, dialetheism, and the divide between Continental/Analytic and Western/Eastern philosophies. Priest shares insights on his transition from mathematics to philosophy, the importance of studying philosophy from diverse traditions, and the value of philosophical skills in various career paths. The interview also touches on the significance of social engagement in philosophy and advises aspiring philosophers to follow their interests and engage with the philosophical community.